A simple and fast sampling method for assessing chemical and nutritional characteristics of pumpkins - Cardoso, Bruno Trindade; Ramos, Semíramis Rabelo Ramalho; lves, Ricardo Elesbão A.; Ledo, Carlos Alberto da Silva; Santos, Antonina dos; Santos, Hister Maria Matias dos (Associação Brasileira de Horticultura, 2020)
In the chemical and nutritional analyses of pumpkin, the size of bulk sample recommended by the method of reference, makes the process time consuming and difficult to execute. The purpose of the present study was to evaluate different sampling methods to indicate the most suitable one to replace reference method to determine the levels of total carotenoids, total soluble solids, and moisture in pumpkin. A completely randomized design was used with four treatments and 18 replications. The proposed methods consisted basically in changing the way of taking bulk samples from the fruits: cylinders method, quartile method, and the slice method. Samples obtained by proposed methods were analyzed for moisture content, total carotenoids and total soluble solids. Results obtained by each proposed method were compared against the method of reference. Cylinders method showed the best results and was the easiest to be carried out, consuming only about 1/10 of the time required in relation to the method of reference. The cylinder method was rapid, efficient, reliable and exhibited the greatest suitability for replacing the reference method.